2019
DOI: 10.1016/j.biomaterials.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Gene to diagnostic: Self immobilizing protein for silica microparticle biosensor, modelled with sarcosine oxidase

Abstract: A rational design approach is proposed for a multifunctional enzyme reagent for point-of-care diagnostics. The biomaterial reduces downstream isolation steps and eliminates immobilization coupling chemicals for integration in a diagnostic platform. Fusion constructs combined the central functional assay protein (e.g. monomeric sarcosine oxidase, mSOx, horseradish peroxidase, HRP), a visualizing protein (e.g. mCherry) and an in-built immobilization peptide (e.g. R5). Monitoring protein expression in E.coli was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 73 publications
2
45
0
Order By: Relevance
“…Gold-mSOx-R5-MPTMS GCE-mSOx-R5-GA over several weeks (as shown previously [6,14]). For the thickest layer, the LOD is reduced to 8 μM, with a dynamic range to 1700 μM.…”
Section: Gce-msox-r5-tmossupporting
confidence: 80%
See 4 more Smart Citations
“…Gold-mSOx-R5-MPTMS GCE-mSOx-R5-GA over several weeks (as shown previously [6,14]). For the thickest layer, the LOD is reduced to 8 μM, with a dynamic range to 1700 μM.…”
Section: Gce-msox-r5-tmossupporting
confidence: 80%
“…Importantly, this result shows that the biosilification only requires one protein to contain the R5 tag. However, we have previously shown that without the R5, the immobilisation is not stable [6]. The data reported herein provide a basis to further expand the manufacturing techniques for use in low resource areas and to contribute to the challenge of delivering sustainable diagnostics in these environments.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations